Digital Empowerment of Women Entrepreneurs for Competitive Advantage and Poverty Reduction - Muchammad Firman Mauludin; Pesta Asni W Napitupuluh; Eny Yuniyati (Jobmark: Journal of Branding and Marketing Communication, 2025)
Poverty in East Java remains a persistent, multidimensional challenge, particularly in disadvantaged regions such as Tapal Kuda, where structural constraints limit economic mobility. This study examines how e-commerce functions as a strategic capability in strengthening women’s entrepreneurship, generating competitive advantage, and reducing poverty vulnerability. Adopting an interpretive qualitative case study approach, data were collected through in-depth interviews, observations, and document analysis of women-led MSMEs that use marketplace platforms, and were analyzed thematically through a Resource-Based View (RBV) lens. The findings reveal that e-commerce operates not merely as a transactional channel but as a strategic digital resource that enables market expansion, network integration, and competitive positioning. Women entrepreneurs develop digital differentiation through packaging innovation, localized branding, and interactive consumer engagement, which enhances business resilience and income generation. These practices contribute to household economic stability and reinforce women’s socio-economic roles. However, sustainability is constrained by limited digital literacy, infrastructural gaps, and insufficient institutional support. Theoretically, this study extends RBV by situating digital capabilities within gendered entrepreneurial contexts in disadvantaged regions. Practically, it highlights the need for integrated policies that foster digital ecosystems for women’s entrepreneurship, including infrastructure development, capacity building, inclusive financing, and value chain integration.